Introduction to programming concepts with case studies in python - Üçoluk, Göktürk (Springer Vienna, 2012)
The current text provides a clear introduction to Computer Science concepts in a programming  environment. It is designed as suitable use in freshman- or introductory level coursework in CS and provides the fundamental concepts as well as abstract  theorems for solving computational problems. The Python language serves as a medium for illustrating and demonstrating the concepts.